PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN APLIKASI DISCORD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP MUHAMMADIYAH 12 BINJAI - Kiki Puspita Dewi (Jurnal Bilqolam Pendidikan Islam, 2022)
The problem that arises is the lack of learning media in the learning process, especially in this day and age, learning media have developed very widely. Especially during the pandemic, the school only used the WhatsApp application, and it didn't work well, and it would affect the learning outcomes of students. Therefore, of course, from the pandemic period that transformed into the new normal period, their learning outcomes will also experience changes. To view t Table dk= + - 2 = 17+17-2 = 32, 349, with the obtained t table at = 0.05 (5%) 2-party test obtained t table = 0.339 It turns out that th > tt then Ha is accepted. So, there is a difference in learning outcomes between the use of discord media, namely the class that uses the application and the control class, namely the conventional class on student learning outcomes of PAI subjects at SMP Muhammadiyah 12 Binjai. It can be seen from the average value between the control class (54.00) and the experimental class (81.00). The effect of using the discord application is proven by the mean whienoy u test, the mean rank of the experimental class is 17.38 and the mean value of the control class is 6.14. this means that the use of the Discord Application is appropriate for online learning.